Fertilización inorgánica en características vegetativas y rendimiento de forraje en rebrote de Pennisetum sp. Cuba 22 en Zungarococha – Loreto. 2023 - Quinteros Paredes, Doris Rubi (2023)
The use of synthetic fertilizers in the production of pastures and forages is one of the practical alternatives used in many places. The Faculty of Agronomy of the UNAP of the Loreto region, knows the importance and proposes the present work: "INORGANIC FERTILIZATION IN VEGETATIVE CHARACTERISTICS AND FORAGE YIELD IN REGROUND Peniseum sp. CUBA 22 IN ZUNGAROCOCHA – LORETO. 2023", a Completely Random Block Design with 4 treatments and 4 repetitions was used. The treatments under study were: T1 (0 kilos of Bayfolan/ha), T2 (50 kilos of Bayfolan/ha), T3 (100 kilos of Bayfolan nitrogen/ha) and T4 (150 kilos of Bayfolan/ha). Reaching the following conclusions: That the higher the dose of the inorganic fertilizer Bayfolan blue soil, the values of the dependent variables increased. Regarding the agronomic characteristics, the T4 treatment (150 kilos of Bayfolan blue soil/ha) obtained the best results as plant height with 2.02 meters, leaf: stem ratio of 0.54. Regarding yield, the T4 treatment (150 kilos of Bayfolan blue soil/ha) gave the best results as green matter of 10.08 kg/m2, dry matter of 2.42 kg/m2 and yield of 100,850 kilos per hectare.